Determinants of placental leptin receptor gene expression and association with measures at birth. (October 2020) - Vlahos, Amanda; Mansell, Toby; Burgner, David; Collier, Fiona; Novakovic, Boris; Saffery, Richard; Vuillermin, Peter; Collier, Fiona; Ponsonby, Anne-Louise; Carlin, John; Allen, Katie; et al.
Abstract: Introduction: The leptin signalling pathway is important in metabolic health during pregnancy. However, few studies have investigated the determinants and extent of leptin receptor gene ( LEPR ) expression in the placenta, nor the relationship with infant health in early life. Here, we investigate the genetic and maternal in utero determinants of placental LEPR expression, and whether this expression is linked to anthropometric and inflammatory measures at birth in healthy newborns in the Barwon Infant Study. Methods: Placental LEPR expression was measured using RT-qPCR (n = 854 placentae). Associations between genetic variation in LEPR, maternal in utero factors, measures at birth and placental LEPR expression were assessed using multivariable linear regression modelling. Results: We found that the genotype at two intronic SNPs, rs9436301 and rs9436746, was independently associated with placental LEPR expression. Maternal pre-pregnancy body mass index, gestational diabetes mellitus, weight gain and smoking in pregnancy were not associated with LEPR expression. Placental LEPR expression was negatively associated with high sensitivity C-Reactive Protein in umbilical cord blood, which persisted after adjustment for potential confounders. Discussion: Overall, our findings suggest that genetic variation in LEPR plays a key role in regulating placental LEPR expression, which is in turn is associated with inflammatory markers in cord blood at birth. Further studies encompassing other aspects of leptin signalling are warranted to understand if these relationships are causal and have health implications. Highlights: Maternal factors are not a key determinant of placental LEPR expression. Genetic variation in LEPR is a key determinant of placental LEPR expression. Placental LEPR expression is associated with inflammation in umbilical cord blood.